Intramural unicystic ameloblastoma in upper jaw. A case report - Valecillos Fuenmayor, Mariangela Victoria (2018)
Unicystic Ameloblastoma (UA) accounts for approximately 6% of all ameloblastomas. They are often observed during the second decade of life, without a predilection for gender, with 90% of the lesions occurring in the jaw and related to an unerupted tooth. Unicystic ameloblastoma shows clinical and radiographic features similar to maxillary cysts but histologically evidences ameloblastic epithelium. The lesion has a less aggressive biological behavior than solid ameloblastoma, with a lower recurrence rate compared with conservative treatment, however, a radical therapeutic is recommended for the intramural variant. The aim of the present work was to describe a case of UA located in the maxilla of a 26-year-old male patient, who showed an increase in volume in the right hemiface of five months of evolution. The histopathological examination of the specimen obtained by the incisional biopsy was UA Intramural; In a second surgical tempo, a hemimaxilectomy was performed on the affected side using an intra-oral approach. Long-term follow-up of these lesions is recommended to assess the possibility of relapse and an interdisciplinary therapeutic-rehabilitation approach.